Peran Kualitas Pelayanan dan Pengaruh Harga terhadap Kepuasan Pelanggan - Putu Erni Rismayanti; Ni Luh Wayan Sayang Telagawathi; A.A.N. Yudha Martin Mahardika (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the role of service quality and the effect of price on customer satisfaction at UD Bala Bala Karangasem. The type of research used is quantitative. The subjects in this study were customers at UD Bala Bala Karangasem, while the objects in this study were price, service quality, and customer satisfaction. The population used in this study were customers of UD Bala Bala Karangasem. The number of samples used in this study were 100 respondents. Data were collected by questionnaire method, and analyzed by path analysis. The results showed that (1) price had a positive and significant effect on customer satisfaction at UD Bala Bala Karangasem, (2) service quality had a positive and significant effect on customer satisfaction at UD Bala Bala Karangasem, (3) price had a positive and significant effect on service quality. at UD Bala Bala Karangasem, and (4) price has a positive effect on customer satisfaction through service quality at UD Bala Bala Karangasem.